Implementation of the Blended E-Learning Model in Improving PAI Learning Outcomes for SMA Negeri 1 Mamuju Students - Alfian Yusuf; Usman; Abd. Halik; Sitti Jamilah Amin; Muh. Dahlan (Universitas Muhammadiyah Palu, 2023)
The objectives of this research are 1) to determine the implementation of blended e-learning media models at SMA Negeri 1 Mamuju. 2) find out the PAI learning outcomes of students at SMA Negeri 1 Mamuju who use the blended e-learning media model. The type of research used is qualitative research, and the research instruments used are observation, interviews, and documentation. The study lasted five months and took place at SMA Negeri 1 Mamuju. The primary data source was from interviews with the principal, 2 PAI teachers (MIPA and IPS), and 25 students of SMA Negeri 1 Mamuju who had medium grades, while the secondary data source was taken from recommended books, journals, or written works. The data analysis technique used is data reduction, data presentation, and conclusion drawing, and the data validity technique used by researchers is the credibility test. The results of this research show that: 1) Implementation of the use of the blended e-learning model at SMA Negeri 1 Mamuju, the learning concept implemented by PAI teachers at SMA Negeri 1 Mamuju in the implementation process was carried out in two models, namely online and face to face, carried out three times. For online and five times for face-to-face learning in six classes in one semester, this is by the composition of the blended e-learning learning pattern. In implementing the blended e-learning model, teachers at SMA Negeri 1 Mamuju implemented it in 3 stages: planning, implementation, and evaluation. 2) PAI learning outcomes of students at SMA Negeri 1 Mamuju using the blended e-learning model, the learning outcomes of SMA Negeri 1 Mamuju students in PAI subjects improve student learning outcomes by looking at the responses of students who like the implementation of blended e-learning. -learning as a method in the learning process can attract students' attention when the learning material takes place in class.